Religiosity indicator as part of subjective well-being for Muslim migrant workers in Malaysia Oil Palm Plantation - Akmal , Chyairreil Annwar; Abdul Mutalib , Mahazan; Wan Razali, Wan Mohd. Fazrul Azdi (Journal of Islamic, Social, Economics and Development, 2025)
Palm oil is one of the largest contributors to Malaysia's economy and accounts for 8.5% of global oil and fat production. It was estimated that a total of 429,351 laborers worked in the plantation sector in 2016 and out of this total, 77% or 330,185 were foreign workers, with most of them coming from Indonesia and Bangladesh. Despite being a renowned palm oil producer, this sector is highly dependent on migrant workers. There are several issues beleaguering this sector, particularly labor, that disrupt their well-being. Among the common labor issues are labor exploitation, debt bondage, abuse of vulnerability, deception, and restriction of movement. These issues are commonly associated with the well-being of workers. Therefore, the primary objective of this study is to explore the indicators of well-being among Muslim migrant workers in oil palm plantation in Malaysia. The study adopts a qualitative approach and semi-structured interviews as data collection. By using word frequency and thematic analysis, among the findings from this study suggested that religiosity indicator play a vital role in influencing the well-being of the Muslim migrant workers. Therefore, the emergence of religiosity indicator may provide a more comprehensive evaluation of well-being from different perspectives and relevant to the actual situation.